If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=4x+9=
We move all terms to the left:
3x-(4x+9)=0
We get rid of parentheses
3x-4x-9=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9
| -216=-8(7+5x) | | -4(p+21)=88 | | 8x-3x+102=8x+57 | | 36-6=5y | | 2=z2 | | 8(1+3n)=-112 | | 4(v+2)=3(v+5 | | 3x+15=6x–6 | | -3-5(1-5x)=192 | | 20=y*4 | | 20=y.4 | | b-7/4=2/3 | | -12+3v+18v=18+19v | | 7+3x=2x+2= | | p=6-9=11 | | 5.6+y=15 | | X+4-3x=4 | | -6(2x-3)=-12-18 | | 50/n=2n | | -250=25x+-75 | | 5+5=x2 | | 9(2x-9.5)=16.5+8x= | | z/2=-15 | | 9(4b−1)=2(9b+3) | | 42+4y-10=180 | | 8x-5=12x-15 | | 65-x=42.25 | | 16x+3x=28 | | 2x+x+10=70 | | 59/n=2n | | 211=45-u | | 5(x-25)=-10x+20 |